Vietnam Inbound M&A Activity: The Role of Government Policy and Regulatory Environment - Hosseini, Jamshid C.; Thu, Nguyen Kim; Trang, Nguyen Thi Thuy (The South East Asian Journal of Management, 2017)
With a robust recent history of reform and opening, joining of the World Trade Organization, and negotiating a myriad of regional and global trade agreements, Vietnam has emerged as a promising destination for foreign direct investment (FDI) and cross-border mergers and acquisitions (M&A). In this paper, we provide an overview of Vietnam’s inbound mergers and acquisitions and review the two main driving forces of inbound M&A, which are the legal framework reform process and the equitization of State-owned enterprises. We close by providing directions for future research in the area of cross-border M&As.